Application of X-ray Fluorescence and Radiation Methods for the Analysis of Medicinal Plant Raw Materials on the Example of Achilleae millefolii herba - I. Yu. Kalikina; A. Yu. Turyshev; V. D. Belonogova; A. V. Kuritsyn; S. V. Puchnina; N. A. Buzmakova (Разработка и регистрация лекарственных средств)
Introduction. Environmental monitoring is an important area of modern scientific research. This is due to the anthropogenic impact on the environment, which often negatively affects the diversity of the Russian medicinal flora. The use of modern instrumental analytical methods of medicinal plant raw materials is relevant due to the intensive development of science. The content of heavy metals, the elemental composition and the level of background radiation are important characteristics of ecological purity and safety of medicinal plant raw materials. These characteristics are of interest for assessing the possibility of harvesting and using medicinal plants at localization. The generally accepted instructions for harvesting were used.Aim. Investigation of the possibilities of using X-ray fluorescence and radiation methods for environmental monitoring of medicinal plant raw materials.Materials and methods. The research object was Achilleae millefolii herba. The harvestment of plant raw materials was carried out in the Bardymsky, Chernushinsky, Uinsky, Kishertsky, Oktyabrsky, Suksunsky, Ordinsky, Sivinsky districts of the Perm Region in the summer in 2022–2023. The X-ray fluorescence analyzer (XFA) ARL QUANT'X EDXRF was used to determine heavy metals and assess the elemental composition of plants. The analysis was carried out according to the methodology that was developed by scientists of the Pharmacognosy Department at the Perm State Pharmaceutical Academy. The radiation background in raw materials was assessed by using a special dosimeter RADEX RD1503.Results and discussion. As a result, it was found that harvesting of Achilleae millefolii herba is possible in the Perm Region studied areas. Bardymsky, Uinsky, Kishertsky, Ordinsky, Chernushinsky districts are the most recommended for harvesting plant raw materials. Samples from these areas are ecological purity and safe for use as medicinal raw materials and have a diverse elemental composition. The content of heavy metals does not exceed the maximum permissible concentrations according to the regulatory documentation requirements. The background radiation level does not exceed the threshold value compared to other areas in the Russian Federation.Conclusion. X-ray fluorescence analysis is a suitable and reliable analytical method for determining elements in plant raw materials. XFA is a multi-element express method that allows analyzing a sample with minimal sample preparation. The advantages of the method are good reproducibility, high sensitivity, and efficiency. Research continues.